Is this advertisement designed to appeal to you? Adolescents' views about Instagram advertisements promoting ultra-processed products - Gastón Ares; Lucía Antúnez; Florencia Alcaire; Virginia Natero; Tobias Otterbring (Cambridge University Press, 2024)
Abstract Objective: Examine the key elements that characterise social media advertisements targeted at adolescents by asking adolescents which features of Instagram ads promoting ultra-processed products make them designed to appeal to adolescents. Design: Instagram ads promoting ultra-processed products and brands were selected from a database in which ads had been classified regarding whether they were primarily targeted at adolescents from an adult perspective. Adolescents completed a sorting task in small groups and were requested to reach a consensus through discussions and sticky notes regarding whether sixty ads were designed to appeal to them. The sorting task was analysed using content analysis based on inductive coding. Setting: One private secondary school and two after-school clubs. Participants: Convenience sample of 105 Uruguayan adolescents aged 11-17 years. Results: Ten categories were identified regarding the reasons for sorting ads as (not) designed to appeal to adolescents: product type, graphic design, explicit references to age groups, language, activities or themes, memes, celebrities, characters, promotions and novelty. Product type emerged as a key element, with adolescents perceiving ads as designed to appeal to them simply because they promoted specific products. Conclusions: This research contributes to the validation of criteria defined in previous studies and can be used for the development of tools to monitor the prevalence and power of adolescent-targeted digital marketing. However, the importance attributed to type of product suggests that regulations should not exclusively focus on exposure to digital marketing specifically targeted at adolescents but also on exposure to marketing in general.